Things papers on objects, events, and properties - Yablo, Stephen (Oxford : Oxford University Press, 2010)
This is a collection of 12 essays on identity, essence causation, properties, ontology, and metaontology, with an emphasis on the metaontology of abstract objects. Almost all of Yablo's published work on these topics is collected here, along with the previously unpublished 'Carving Content at the Joints'.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Metaphysics